Human placenta-derived mesenchymal stem cells stimulate ovarian function via miR-145 and bone morphogenetic protein signaling in aged rats - Kyeoung-Hwa Kim; Eun-Young Kim; Gi Jin Kim; Jung-Jae Ko; Kwang Yul Cha; Mi Kyung Koong; Kyung-Ah Lee (Stem Cell Research & Therapy, 2020)
Abstract Background Aging has detrimental effects on the ovary, such as a progressive reduction in fertility and decreased hormone production, that greatly reduce the quality of life of women. Thus, the current study was undertaken to investigate whether human placenta-derived mesenchymal stem cell (hPD-MSC) treatment can restore the decreases in folliculogenesis and ovarian function that occur with aging. Methods Acclimatized 52-week-old female SD rats were randomly divided into four groups: single hPD-MSC (5 × 105) therapy, multiple (three times, 10-day intervals) hPD-MSC therapy, control (PBS), and non-treated groups. hPD-MSC therapy was conducted by tail vein injection into aged rats. The rats were sacrificed 1, 2, 3, and 5 weeks after the last injection. hPD-MSC tracking and follicle numbers were histologically confirmed. The serum levels of sex hormones and circulating miRNAs were detected by ELISA and qRT-PCR, respectively. TGF-β superfamily proteins and SMAD proteins in the ovary were detected by Western blot analysis. Results We observed that multiple transplantations of hPD-MSCs more effectively promoted primordial follicle activation and ovarian hormone (E2 and AMH) production than a single injection. After hPD-MSC therapy, the levels of miR-21-5p, miR-132-3p, and miR-212-3p, miRNAs associated with the ovarian reserve, were increased in the serum. Moreover, miRNAs (miR-16-5p, miR-34a-5p, and miR-191-5p) with known adverse effects on folliculogenesis were markedly suppressed. Importantly, the level of miR-145-5p was reduced after single- or multiple-injection hPD-MSC therapy, and we confirmed that miR-145-5p targets Bmpr2 but not Tgfbr2. Interestingly, downregulation of miR-145-5p led to an increase in BMPR2, and activation of SMAD signaling concurrently increased primordial follicle development and the number of primary and antral follicles. Conclusions Our study verified that multiple intravenous injections of hPD-MSCs led to improved ovarian function via miR-145-5p and BMP-SMAD signaling and proposed the future therapeutic potential of hPD-MSCs to promote ovarian function in women at advanced age to improve their quality of life during climacterium.